Secondary battery and electronic device
By adding fast ion conductors and using high-temperature resistant separators to the negative electrode system of lithium-ion batteries, the deformation problem caused by moisture generated by the battery is solved, and its circulation and safety performance are improved.
Patent Information
- Application Number
- CN202311264752.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-03-28
AI Technical Summary
During the preparation and use of lithium-ion batteries, gas will be generated due to the presence of moisture, which will cause the battery to deform, affecting its circulation and safety performance.
Add fast ion conductors, such as lithium lanthanum zirconium oxide, to the negative electrode system of the secondary battery, and use a high-temperature resistant separator to ensure that the heat shrinkage rate of the separator at 150°C is less than or equal to 1.5%.
By adding fast ion conductors and using high-temperature resistant separators, the drying temperature of the battery is increased, the water content is reduced, the hydrogen production is reduced, and the circulation and safety performance of the battery is improved.
Smart Images

Figure CN119725531A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical technology, and in particular to a secondary battery and an electronic device. Background Art
[0002] Secondary batteries (such as lithium-ion batteries) have the characteristics of large specific energy, high operating voltage, low self-discharge rate, small size and light weight, and are widely used in the field of consumer electronics.
[0003] With the widespread application of lithium-ion batteries, the market has put forward higher and higher requirements on the performance of lithium-ion batteries. At present, during the preparation and use of lithium-ion batteries, gas will be generated due to the presence of water, which will cause the lithium-ion battery to deform and affect the cycle performance and safety performance of lithium-ion batteries. Summary of the invention
[0004] The purpose of this application is to provide a secondary battery and an electronic device to improve the cycle performance and safety performance of the secondary battery. The specific technical solution is as follows:
[0005] The first aspect of the present application provides a secondary battery, comprising a positive electrode plate, a negative electrode plate and a separator, wherein the separator is arranged between the positive electrode plate and the negative electrode plate, the negative electrode plate comprises a negative electrode current collector and a negative electrode material layer arranged on at least one surface of the negative electrode current collector, the negative electrode material layer comprises a negative electrode active material and a fast ion conductor, at least part of the fast ion conductor is arranged on the surface of the negative electrode active material, and the fast ion conductor is lithium lanthanum zirconium oxide; based on the total mass of the negative electrode material layer, the mass percentage of the fast ion conductor is 0.1% to 16%; the thermal shrinkage rate of the separator at 150°C is less than or equal to 1.5% (it can also be called a high temperature resistant separator), preferably, the thermal shrinkage rate of the high temperature resistant separator at 150°C is less than or equal to 0.6%. When a fast ion conductor is added to the negative electrode system of a secondary battery and the secondary battery uses the separator, and the mass percentage of the fast ion conductor and the thermal shrinkage rate of the separator at 150°C are within the scope of this application, the drying temperature of the secondary battery preparation process can be increased, the overall water content of the secondary battery can be reduced, and the hydrogen generation caused by the high water content can be reduced, which helps the fast ion conductor to better play its role in absorbing and producing gas, thereby effectively improving the cycle performance and safety performance of the secondary battery.
[0006] In one embodiment of the present application, the high temperature resistant membrane includes one of a cellulose membrane, a polyimide membrane, a polyester membrane, an aramid membrane or a spandex membrane. The high temperature resistant membrane has good high temperature resistance. By selecting the high temperature resistant membrane, the safety performance of the secondary battery can be improved, and the drying temperature in the secondary battery preparation process can be increased, and the overall water content of the secondary battery can be reduced, thereby improving the cycle performance of the secondary battery.
[0007] In one embodiment of the present application, the thickness of the high temperature resistant separator is H1 μm, 5≤H1≤30. By adjusting the value of H1 within the scope of the present application, the energy density of the secondary battery can be guaranteed while improving the cycle performance and safety performance of the secondary battery.
[0008] In one embodiment of the present application, the Dv50 of the negative electrode active material is D1μm, the Dv50 of the fast ion conductor is D2μm, D2 / D1≤0.1, preferably, 0.03≤D2 / D1≤0.07; and 0.05≤D2≤1, preferably, 0.3≤D2≤0.7. By regulating the value of D2 / D1 and the value of D2 within the scope of the present application, the fast ion conductor can form a more stable solid-state electrolyte membrane on the surface of the negative electrode active material together with the solid electrolyte layer (SEI layer) generated during the formation process, making the negative electrode active material more stable, further suppressing the gas production of the secondary battery, and at the same time, the fast ion conductor can also better play its role in absorbing the gas production of the secondary battery, further improving the cycle performance and safety performance of the secondary battery.
[0009] In one embodiment of the present application, 5≤D1≤20. By adjusting the value of D1 within the scope of the present application, the particle size of the negative electrode active material can be better matched with the particle size of the fast ion conductor, so that the fast ion conductor forms a more stable solid-state electrolyte membrane together with the SEI layer generated during the formation process on the surface of the negative electrode active material, further improving the cycle performance and safety performance of the secondary battery.
[0010] In one embodiment of the present application, the Dv99 of the fast ion conductor is D3 μm, 0.15≤D2 / D3<1. By adjusting the value of D2 / D3 within the scope of the present application, the fast ion conductor can have a suitable particle size distribution, and can form an effective solid-state electrolyte film on the surface of the negative electrode active material, further improving the cycle performance and safety performance of the secondary battery.
[0011] In one embodiment of the present application, 0.5<D3≤4. By adjusting the value of D3 within the scope of the present application, the uniformity of the fast ion conductor particles can be higher, the processing cost of the fast ion conductor can be lowered, and the particle size of the fast ion conductor can be better matched with the particle size of the negative electrode active material, thereby improving the cycle performance and safety performance of the secondary battery.
[0012] In one embodiment of the present application, the ionic conductivity of the fast ion conductor is 1.44×10 -5 S / m to 1.09×10 -3 By regulating the ionic conductivity of the fast ion conductor within the scope of the present application, the conductivity of the negative electrode active material can be increased, which helps to further improve the cycle performance of the secondary battery.
[0013] In one embodiment of the present application, the lithium lanthanum zirconium oxide has a molecular formula of any one of formula (A), formula (B) or formula (C):
[0014] Li α M β La3Zr2O 12 (A)
[0015] In formula (A), M includes at least one of Ga, Al or Fe, satisfying: α+3β=7, α≥5.5, β≥0;
[0016] 7La γ R δ Zr2O 12 (B)
[0017] In formula (B), R is at least one of Ce or Y, satisfying: 3γ+3δ=9, γ≥2.5, δ≥0;
[0018] Li7La3Zr a X b Q c O 12 (C)
[0019] In formula (C), X and Q are each independently selected from at least one of Ta, Nb, Sn, Sb, W, Te, Cr or Y, satisfying: a+b+c=2, a≥1, b≥0, c≥0. By selecting the above lithium lanthanum zirconium oxide, the electrochemical window of the undoped lithium lanthanum zirconium oxide can be expanded, and the electrochemical stability of the lithium lanthanum zirconium oxide can be increased, so that it can serve as a more stable and efficient transition layer for conducting lithium ions, which is beneficial to improving the gas production of the secondary battery and further improving the cycle performance and safety performance of the secondary battery.
[0020] In one embodiment of the present application, the lithium lanthanum zirconium oxide comprises Li7La3Zr2O 12 , Li 6.28 Al 0.24 La3Zr2O 12 , Li 6.25 Ga 0.25 La3Zr2O 12 , Li 6.4 Ga 0.2 La3Zr2O 12 、Li7La 2.5 Ce 0.5 Zr2O 12 、Li7La 2.875 Y 0.125 Zr2O 12 or Li7La3ZrNb0.5 Y 0.5 O 12 By selecting the above-mentioned lithium lanthanum zirconium oxide, an effective solid-state electrolyte membrane can be formed on the surface of the negative electrode active material, which can provide a lithium ion diffusion channel and inhibit the side reaction between the negative electrode active material and the electrolyte, protect the negative electrode active material, improve the gas production of the secondary battery, and improve the cycle performance and safety performance of the secondary battery.
[0021] In one embodiment of the present application, the negative electrode material layer further includes a binder and a conductive agent, and based on the total mass of the negative electrode material layer, the mass percentage of the negative electrode active material is 80% to 98%, and the sum of the mass percentages of the binder and the conductive agent is 1% to 4%. By regulating the mass percentages of the negative electrode active material, the binder, and the conductive agent within the scope of the present application, the secondary battery can have a higher energy density while improving the cycle performance and safety performance of the secondary battery.
[0022] The second aspect of the present application provides an electronic device, which includes the secondary battery in any of the above embodiments. Therefore, the electronic device provided by the present application has good performance.
[0023] Beneficial effects of this application:
[0024] The embodiment of the present application provides a secondary battery and an electronic device, wherein the secondary battery comprises a positive electrode sheet, a negative electrode sheet and a separator, wherein the separator is arranged between the positive electrode sheet and the negative electrode sheet, wherein the negative electrode sheet comprises a negative electrode current collector and a negative electrode material layer arranged on at least one surface of the negative electrode current collector, wherein the negative electrode material layer comprises a negative electrode active material and a fast ion conductor, wherein at least part of the fast ion conductor is arranged on the surface of the negative electrode active material, and the fast ion conductor is lithium lanthanum zirconium oxide; based on the total mass of the negative electrode material layer, the mass percentage of the fast ion conductor is 0.1% to 16%; and the thermal shrinkage rate of the separator at 150°C is less than or equal to 1.5%. When a fast ion conductor is added to the negative electrode system of the secondary battery, and the secondary battery uses the separator at the same time, and the mass percentage of the fast ion conductor and the thermal shrinkage rate of the separator at 150°C are within the scope of the present application, the cycle performance and safety performance of the secondary battery can be improved.
[0025] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other embodiments can also be obtained based on these drawings.
[0027] Figure 1 This is a schematic diagram of a structure in which a fast ion conductor is distributed on the surface of a negative electrode active material in one embodiment of the present application;
[0028] Figure 2 This is a scanning electron microscope image of the cellulose membrane in Example 1-1 of the present application. DETAILED DESCRIPTION
[0029] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.
[0030] It should be noted that in the specific implementation manner of the present application, the present application is explained by taking a lithium-ion battery as an example of a secondary battery, but the secondary battery of the present application is not limited to a lithium-ion battery.
[0031] The present application provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet and a separator, wherein the separator is arranged between the positive electrode sheet and the negative electrode sheet, the negative electrode sheet comprises a negative electrode current collector and a negative electrode material layer arranged on at least one surface of the negative electrode current collector, the negative electrode material layer comprises a negative electrode active material and a fast ion conductor, and at least part of the fast ion conductor is arranged on the surface of the negative electrode active material, such as Figure 1 As shown, the fast ion conductor 2 is distributed on the surface of the negative electrode active material 1. The fast ion conductor is lithium lanthanum zirconium oxide, and based on the total mass of the negative electrode material layer, the mass percentage content W1 of the fast ion conductor is 0.1% to 16%. Exemplarily, the mass percentage content W1 of the fast ion conductor can be 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16% or a range consisting of any two of the above values. The thermal shrinkage rate of the diaphragm at 150°C is less than or equal to 1.5%. Preferably, the thermal shrinkage rate of the diaphragm at 150°C is less than or equal to 0.6%. Exemplarily, the thermal shrinkage rate of the diaphragm at 150°C may be less than or equal to 1.5%, less than or equal to 1.3%, less than or equal to 1.1%, less than or equal to 1%, less than or equal to 0.9%, less than or equal to 0.7%, less than or equal to 0.6%, less than or equal to 0.5%, less than or equal to 0.4%, or less than or equal to 0.3%.
[0032] The inventors have found that adding a fast ion conductor to the negative electrode system of a secondary battery can improve the stability and safety of the secondary battery. However, since water is used as a solvent in the preparation of the negative electrode slurry, and the fast ion conductor has certain water absorption properties, adding a fast ion conductor to the negative electrode system of the secondary battery faces the problem of easy moisture absorption and difficulty in removing trace water, which makes its practical application face certain difficulties. In addition, secondary batteries currently generally use polyethylene (PE) diaphragms, and the high temperature resistance of PE diaphragms is poor. It will shrink and deform at 130°C, which limits the drying temperature in the preparation process of the secondary battery (currently when the secondary battery uses a polyethylene diaphragm, the drying temperature in the preparation process is generally 80°C to 90°C). Higher drying temperatures can cause the secondary battery to short-circuit and fail. When a fast ion conductor is added to the negative electrode system of a secondary battery and the secondary battery uses the diaphragm, and the mass percentage of the fast ion conductor and the thermal shrinkage of the diaphragm at 150°C are within the scope of the present application, the above-mentioned diaphragm has a small thermal shrinkage at 150°C, can support the drying process of the secondary battery at a higher temperature (for example, greater than or equal to 150°C), can increase the drying temperature of the back-end process (for example, the drying process after injecting the electrolyte), reduce the overall water content of the secondary battery, reduce the hydrogen production caused by high water content, and help the fast ion conductor to better play its role in absorbing and producing gas, thereby effectively improving the cycle performance and safety performance of the secondary battery.
[0033] In the present application, "at least part of the fast ion conductor is arranged on the surface of the negative electrode active material" means that the fast ion conductor may exist on part of the surface of the negative electrode active material or on the entire surface. This application has no special restrictions as long as the purpose of this application can be achieved.
[0034] In one embodiment of the present application, the high temperature resistant membrane includes one of a cellulose membrane, a polyimide membrane, a polyester membrane, an aramid membrane or a spandex membrane. The above-mentioned high temperature resistant membrane has good high temperature resistance. By selecting the above-mentioned high temperature resistant membrane, the safety performance of the secondary battery can be improved, and the drying temperature in the secondary battery preparation process can be increased, and the overall water content of the secondary battery can be reduced, thereby improving the cycle performance of the secondary battery.
[0035] In one embodiment of the present application, the thickness of the high temperature resistant diaphragm is H1 μm, 5≤H1≤30, and illustratively, the thickness H1 of the high temperature resistant diaphragm can be 5, 7, 9, 10, 13, 15, 17, 19, 20, 23, 25, 27, 29, 30, or a range consisting of any two of the above values. By adjusting the value of H1 within the scope of the present application, the energy density of the secondary battery can be ensured while improving the cycle performance and safety performance of the secondary battery.
[0036] The present application has no particular restrictions on the method for regulating the heat shrinkage rate of the high temperature resistant diaphragm at 150°C, as long as the purpose of the present application can be achieved. For example, the heat shrinkage rate of the high temperature resistant diaphragm at 150°C can be regulated by regulating the type of the high temperature resistant diaphragm. For example, the heat shrinkage rate of the high temperature resistant diaphragm at 150°C can be reduced by coating an inorganic ceramic on the surface of the high temperature resistant diaphragm.
[0037] In one embodiment of the present application, the Dv50 of the negative electrode active material is D1 μm, the Dv50 of the fast ion conductor is D2 μm, D2 / D1≤0.1, preferably, 0.03≤D2 / D1≤0.07, and illustratively, D2 / D1 can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1 or any two of the above values. range; and 0.05≤D2≤1, preferably, 0.3≤D2≤0.7, illustratively, D2 can be 0.05, 0.09, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1 or a range consisting of any two of the above values. By regulating the value of D2 / D1 and the value of D2 within the scope of this application, the fast ion conductor can form a more stable solid-state electrolyte membrane on the surface of the negative electrode active material together with the SEI layer generated during the formation process, making the negative electrode active material more stable, further suppressing the gas production of the secondary battery, and at the same time, the fast ion conductor can also better play its role in absorbing the gas production of the secondary battery, further improving the cycle performance and safety performance of the secondary battery.
[0038] In the present application, Dv50 refers to the particle size at which the volume accumulation is 50% measured from the smallest particle size in the volume-based particle size distribution of the material.
[0039] In one embodiment of the present application, 5≤D1≤20, illustratively, D1 can be 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 or a range consisting of any two of the above values. By adjusting the value of D1 within the scope of the present application, the particle size of the negative electrode active material can be better matched with the particle size of the fast ion conductor, so that the fast ion conductor forms a more stable solid-state electrolyte membrane on the surface of the negative electrode active material together with the SEI layer generated during the formation process, further improving the cycle performance and safety performance of the secondary battery.
[0040] In one embodiment of the present application, the Dv99 of the fast ion conductor is D3 μm, 0.15≤D2 / D3<1, and illustratively, D2 / D3 can be 0.15, 0.2, 0.25, 0.29, 0.3, 0.35, 0.39, 0.4, 0.45, 0.49, 0.5, 0.55, 0.59, 0.6, 0.65, 0.67, 0.69, 0.7, 0.75, 0.79, 0.8, 0.85, 0.89, 0.9, 0.95, 0.99 or a range consisting of any two of the above values. By regulating the value of D2 / D3 within the scope of the present application, the fast ion conductor can have a suitable particle size distribution, can form an effective solid-state electrolyte film on the surface of the negative electrode active material, and further improve the cycle performance and safety performance of the secondary battery.
[0041] In the present application, Dv99 refers to the particle size reaching 99% of the volume accumulation measured from the smallest particle size in the volume-based particle size distribution of the material.
[0042] In one embodiment of the present application, 0.5<D3≤4, illustratively, D3 can be 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1, 1.5, 2, 2.5, 3, 3.5, 4 or a range consisting of any two of the above values. By adjusting the value of D3 within the scope of the present application, the uniformity of the fast ion conductor particles can be higher, the processing cost of the fast ion conductor can be lowered, and the particle size of the fast ion conductor can be better matched with the particle size of the negative electrode active material, thereby improving the cycle performance and safety performance of the secondary battery.
[0043] The present application has no particular restrictions on the method of regulating the Dv50 and Dv99 of the above-mentioned fast ion conductors, as long as the purpose of the present application can be achieved. Exemplarily, the Dv50 and Dv99 of the fast ion conductor can be regulated by grinding the fast ion conductor. For example, the Dv50 of the fast ion conductor can be regulated by regulating the grinding time; the Dv99 of the fast ion conductor can be regulated by regulating the grinding time. Exemplarily, when other conditions remain unchanged, extending the grinding time will reduce the Dv50 of the fast ion conductor and reduce the Dv99 of the fast ion conductor; shortening the grinding time will increase the Dv50 of the fast ion conductor and increase the Dv99 of the fast ion conductor.
[0044] The present application does not particularly limit the method for regulating the Dv50 of the negative electrode active material, as long as the purpose of the present application can be achieved. Exemplarily, the Dv50 of the negative electrode active material can be regulated by grinding the negative electrode active material. For example, the Dv50 of the negative electrode active material can be regulated by regulating the grinding time. Exemplarily, when other conditions remain unchanged, the Dv50 of the negative electrode active material decreases when the grinding time is extended; and the Dv50 of the negative electrode active material increases when the grinding time is shortened.
[0045] The present application has no particular limitation on the method for regulating D2 / D1, as long as the purpose of the present application can be achieved. For example, the value of D2 / D1 can be regulated by regulating the values of D2 and D1, and the regulation method is as described above.
[0046] The present application has no particular limitation on the method for regulating D2 / D3, as long as the purpose of the present application can be achieved. For example, the value of D2 / D3 can be regulated by regulating the respective values of D2 and D3, and the regulation method is as described above.
[0047] In one embodiment of the present application, the ionic conductivity of the fast ion conductor is 1.44×10 -5 S / m to 1.09×10 -3 S / m. Specifically, the ionic conductivity of the fast ion conductor can be 1.44×10 -5 S / m, 4×10 -5 S / m, 6×10 -5 S / m, 8×10 -5 S / m, 1×10 -4 S / m, 1.44×10 -4 S / m, 4×10 -4 S / m, 6×10 -4 S / m, 8×10 -4 S / m, 1×10 -3 S / m, 1.09×10 -3 S / m may be a range consisting of any two of the above values. By regulating the ionic conductivity of the fast ion conductor within the scope of the present application, the conductivity of the negative electrode active material can be increased, which helps to further improve the cycle performance of the secondary battery.
[0048] In one embodiment of the present application, the lithium lanthanum zirconium oxide has a molecular formula of any one of formula (A), formula (B) or formula (C):
[0049] Li α M β La3Zr2O 12 (A)
[0050] In formula (A), M includes at least one of Ga, Al or Fe, satisfying: α+3β=7, α≥5.5, β≥0;
[0051] 7La γ R δ Zr2O 12 (B)
[0052] In formula (B), R is at least one of Ce or Y, satisfying: 3γ+3δ=9, γ≥2.5, δ≥0;
[0053] Li7La3Zr a X b Q c O 12 (C)
[0054] In formula (C), X and Q are each independently selected from at least one of Ta, Nb, Sn, Sb, W, Te, Cr or Y, satisfying: a+b+c=2, a≥1, b≥0, c≥0. In the present application, when the lithium lanthanum zirconium oxide contains only four elements of Li, La, Zr and O, it is an undoped lithium lanthanum zirconium oxide. When the lithium lanthanum zirconium oxide has the molecular formula of formula (A) and β is not equal to 0, it is a lithium lanthanum zirconium oxide doped at the Li position; when the lithium lanthanum zirconium oxide has the molecular formula of formula (B) and δ is not equal to 0, it is a lithium lanthanum zirconium oxide doped at the La position; when the lithium lanthanum zirconium oxide has the molecular formula of formula (C), b is not equal to 0 and c is not equal to 0, it is a lithium lanthanum zirconium oxide doped at the Zr position. By selecting the above-mentioned Li-doped lithium lanthanum zirconium oxide, La-doped lithium lanthanum zirconium oxide or Zr-doped lithium lanthanum zirconium oxide, the electrochemical window of undoped lithium lanthanum zirconium oxide can be expanded, and the electrochemical stability of lithium lanthanum zirconium oxide can be increased, making it a more stable and efficient transition layer for conducting lithium ions, which is beneficial to improving the gas production of secondary batteries and further improving the cycle performance and safety performance of secondary batteries.
[0055] In one embodiment of the present application, lithium lanthanum zirconium oxide includes Li7La3Zr2O 12 , Li 6.28 Al 0.24 La3Zr2O 12 , Li 6.25 Ga 0.25 La3Zr2O 12 , Li 6.4 Ga 0.2 La3Zr2O 12 、Li7La 2.5 Ce 0.5 Zr2O 12 、Li7La 2.875 Y 0.125 Zr2O12 or Li7La3ZrNb 0.5 Y 0.5 O 12 By selecting the above-mentioned lithium lanthanum zirconium oxide, an effective solid-state electrolyte membrane can be formed on the surface of the negative electrode active material, which can provide a lithium ion diffusion channel and inhibit the side reaction between the negative electrode active material and the electrolyte, protect the negative electrode active material, improve the gas production of the secondary battery, and improve the cycle performance and safety performance of the secondary battery.
[0056] In one embodiment of the present application, the negative electrode material layer further includes a binder and a conductive agent. Based on the total mass of the negative electrode material layer, the mass percentage W2 of the negative electrode active material is 80% to 98%, and the sum of the mass percentages of the binder and the conductive agent is 1% to 4%. Among them, the mass percentage W3 of the binder is 0.5% to 3%, and the mass percentage W4 of the conductive agent is 0.5% to 1%. By regulating the mass percentages of the negative electrode active material, the binder, and the conductive agent within the scope of the present application, the secondary battery can have a higher energy density while improving the cycle performance and safety performance of the secondary battery.
[0057] In the present application, the negative electrode plate includes a negative electrode current collector and a negative electrode material layer arranged on at least one surface of the negative electrode current collector. The above-mentioned "negative electrode material layer arranged on at least one surface of the negative electrode current collector" means that the negative electrode material layer can be arranged on one surface of the negative electrode current collector along its own thickness direction, or it can be arranged on two surfaces of the negative electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of the negative electrode current collector or a partial area of the negative electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved. This application has no special restrictions on the negative electrode current collector, as long as the purpose of this application can be achieved. For example, it can include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper or a composite current collector, etc.
[0058] The present application has no particular limitation on the negative electrode active material, as long as the purpose of the present application can be achieved. For example, the negative electrode active material may include natural graphite, artificial graphite, mesophase microcarbon beads (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composites, SiO x (0.5<x<1.6), Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structure lithium titanate Li4Ti5O 12, Li-Al alloy or lithium metal, etc. The present application has no particular restrictions on the binder, as long as the purpose of the present application can be achieved, for example, the binder may include but is not limited to polyacrylate, polyimide, polyamide, polyamide-imide, polyvinylidene fluoride, polystyrene butadiene copolymer (styrene butadiene rubber), sodium alginate, polyvinyl alcohol, polytetrafluoroethylene, polyacrylonitrile, sodium carboxymethyl cellulose, potassium carboxymethyl cellulose, sodium hydroxymethyl cellulose or potassium hydroxymethyl cellulose. The present application has no particular restrictions on the conductive agent, as long as the purpose of the present application can be achieved, for example, the conductive agent may include but is not limited to conductive carbon black (Super P), carbon nanotubes (CNTs), carbon fibers, flake graphite, graphene, metal materials or conductive polymers. The above-mentioned conductive carbon black may include but is not limited to acetylene black or Ketjen black. The above-mentioned carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nano-carbon fibers. The metal material may include but is not limited to metal powder and / or metal fiber, and specifically, the metal may include but is not limited to at least one of copper, nickel, aluminum or silver. The conductive polymer may include but is not limited to at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole.
[0059] The present application has no particular restrictions on the thickness of the negative electrode current collector, as long as the purpose of the present application can be achieved, for example, the thickness of the negative electrode current collector is 5μm to 12μm. The present application has no particular restrictions on the thickness of the negative electrode material layer, as long as the purpose of the present application can be achieved, for example, the thickness of the negative electrode material layer on one surface of the negative electrode current collector is 30μm to 250μm. The present application has no particular restrictions on the thickness of the negative electrode pole piece, as long as the purpose of the present application can be achieved, for example, the thickness of the negative electrode pole piece is 50μm to 500μm.
[0060] Optionally, the negative electrode plate may further include a conductive layer, which is located between the negative electrode current collector and the negative electrode material layer. The present application has no particular restrictions on the composition of the conductive layer, which may be a conductive layer commonly used in the art. The conductive layer includes a conductive agent and a binder. The present application has no particular restrictions on the conductive agent and the binder in the conductive layer, which may be at least one of the above conductive agent and the above binder. The present application has no particular restrictions on the mass ratio of the conductive agent and the binder in the conductive layer, and those skilled in the art may select according to actual needs, as long as the purpose of the present application can be achieved.
[0061] In the present application, the positive electrode plate includes a positive electrode current collector and a positive electrode material layer arranged on at least one surface of the positive electrode current collector. The above-mentioned "positive electrode material layer arranged on at least one surface of the positive electrode current collector" means that the positive electrode material layer can be arranged on one surface of the positive electrode current collector along its own thickness direction, or it can be arranged on two surfaces of the positive electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of the positive electrode current collector or a partial area of the positive electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved. This application has no special restrictions on the positive electrode current collector, as long as the purpose of this application can be achieved. For example, it can include aluminum foil, aluminum alloy foil or a composite current collector (such as an aluminum-carbon composite current collector).
[0062] The positive electrode material layer of the present application includes a positive electrode active material. The present application has no particular restrictions on the positive electrode active material, as long as the purpose of the present application can be achieved. For example, the positive electrode active material may include lithium nickel cobalt manganese oxide (such as common NCM811, NCM622, NCM523, NCM111), lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO2), lithium manganate, lithium iron manganese phosphate or lithium titanate. At least one of the positive electrode material layer of the present application also includes a positive electrode conductor and a positive electrode binder. The present application has no particular restrictions on the types of positive electrode conductors and positive electrode binders, as long as the purpose of the present application can be achieved. For example, the positive electrode conductor can be at least one of the above-mentioned conductors, and the positive electrode binder can be at least one of the above-mentioned binders. The present application has no particular restrictions on the mass ratio of the positive electrode active material, the positive electrode conductor, and the positive electrode binder in the positive electrode material layer. Those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved.
[0063] The present application has no particular restrictions on the thickness of the positive electrode current collector, as long as the purpose of the present application can be achieved, for example, the thickness of the positive electrode current collector is 5μm to 20μm. The present application has no particular restrictions on the thickness of the positive electrode material layer, as long as the purpose of the present application can be achieved, for example, the thickness of the positive electrode material layer on one surface of the positive electrode current collector is 30μm to 250μm. The present application has no particular restrictions on the thickness of the positive electrode sheet, as long as the purpose of the present application can be achieved, for example, the thickness of the positive electrode sheet is 50μm to 500μm.
[0064] Optionally, the positive electrode plate may further include a conductive layer, which is located between the positive electrode current collector and the positive electrode material layer. The present application has no particular restrictions on the composition of the conductive layer, which may be a conductive layer commonly used in the art. The conductive layer includes a conductive agent and a binder. The present application has no particular restrictions on the conductive agent and the binder in the conductive layer, which may be at least one of the above conductive agent and the above binder. The present application has no particular restrictions on the mass ratio of the conductive agent and the binder in the conductive layer, and those skilled in the art may select according to actual needs, as long as the purpose of the present application can be achieved.
[0065] In the present application, the secondary battery also includes an electrolyte, and the electrolyte includes a lithium salt and a non-aqueous solvent. The lithium salt may include various lithium salts commonly used in the art, such as at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, Li2SiF6, lithium bis(oxalate borate) (LiBOB) or lithium difluoroborate. The present application has no particular restrictions on the mass percentage of the lithium salt in the electrolyte, as long as the purpose of the present application can be achieved. The present application has no particular restrictions on the non-aqueous solvent, as long as the purpose of the present application can be achieved, for example, it may include but is not limited to at least one of a carbonate compound, a carboxylate compound, an ether compound or other organic solvents. The above-mentioned carbonate compound may include but is not limited to at least one of a chain carbonate compound, a cyclic carbonate compound or a fluorinated carbonate compound. The above-mentioned linear carbonate compound may include but is not limited to at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) or ethyl methyl carbonate (EMC). The above-mentioned cyclic carbonate compound may include but is not limited to at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC) or vinyl ethylene carbonate (VEC). The above-mentioned fluorinated carbonate compound may include but is not limited to at least one of fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate or trifluoromethylethylene carbonate. The above-mentioned carboxylate compound may include but is not limited to at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanolactone, valerolactone or caprolactone. The above-mentioned ether compound may include but is not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate.
[0066] The secondary battery of the present application also includes a packaging bag for containing a positive electrode sheet, a high temperature resistant diaphragm, a negative electrode sheet and an electrolyte, as well as other components known in the art in the secondary battery, and the present application does not limit the above other components. The present application does not specifically limit the packaging bag, and it can be a packaging bag known in the art, as long as it can achieve the purpose of the present application.
[0067] In the present application, the secondary battery may include, but is not limited to: a lithium metal secondary battery, a lithium ion secondary battery (lithium ion battery), a lithium polymer secondary battery or a lithium ion polymer secondary battery, etc.
[0068] The preparation process of the secondary battery of the present application is well known to those skilled in the art, and the present application has no special restrictions. For example, it may include but is not limited to the following steps: stacking the positive electrode sheet, the high temperature resistant diaphragm and the negative electrode sheet in order, and winding and folding them as needed to obtain an electrode assembly of a winding structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it, and then drying, standing, forming, shaping and other processes to obtain a secondary battery; or stacking the positive electrode sheet, the high temperature resistant diaphragm and the negative electrode sheet in order, and then fixing the four corners of the entire stacked structure with tape to obtain an electrode assembly of a stacked structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it, and then drying, standing, forming, shaping and other processes to obtain a secondary battery. The present application has no special restrictions on the drying temperature and drying time, as long as the purpose of the present application can be achieved, for example, the drying temperature is 120°C to 180°C, and the drying time is 2h to 24h. In addition, overcurrent protection elements, guide plates, etc. may be placed in the packaging bag as needed to prevent pressure rise and overcharge and discharge inside the secondary battery. The packaging bag is a packaging bag known in the art, and this application does not limit this.
[0069] The second aspect of the present application provides an electronic device, which includes the secondary battery in any of the above embodiments. Therefore, the electronic device provided by the present application has good performance.
[0070] The present application does not particularly limit the type of electronic device, which can be any electronic device known in the prior art. In some embodiments, the electronic device can include but is not limited to a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.
[0071] Example
[0072] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.
[0073] Test methods and equipment:
[0074] Thermal shrinkage test of high temperature resistant diaphragm at 150°C:
[0075] The lithium-ion battery was disassembled, the diaphragm was separated, and the diaphragm was cut into samples of 150mm×150mm in size. After marking the vertical and horizontal directions of the samples, the original length L0 of the four sides of each sample was measured, accurate to 0.02mm. Then the samples were placed in an oven, kept at 150℃ for 1h, and then the samples were taken out and the length L1 of the same side of the samples was measured again. The thermal shrinkage rate S was calculated as follows:
[0076] S=(L0-L1) / L0×100.
[0077] Where L0 is the original length of a side of the sample before heat treatment (in mm), and L1 is the length of the same side of the sample after heat treatment (in mm). The arithmetic mean of 8 measured values of 2 samples is taken as the thermal shrinkage rate of the sample at 150°C.
[0078] The thermal shrinkage rate of the diaphragm at 90°C is the thermal shrinkage rate of the diaphragm sample tested at 90°C according to the above method.
[0079] Particle size test:
[0080] The Dv50 of the negative electrode active material, the Dv50 and Dv99 of the fast ion conductor were tested using a particle size analyzer (model: MasterSizer 2000).
[0081] Ionic conductivity test:
[0082] Different fast ion conductors were prepared into high-density ceramic sheets (density 0.96) by cold pressing, and gold was sprayed on both ends of the ceramic sheets to make blocking electrodes. The prepared blocking electrodes were subjected to AC impedance testing with a frequency range of 1MHz to 10Hz and a disturbance amplitude of 10mV. The ionic conductivity σ was calculated as follows: σ=d / Re×S.
[0083] Where d is the thickness of the sample under test (in cm); Re is the body impedance of the sample under test (in ohm), which can be obtained from the intersection of the semicircle arc and the oblique line in the Nyquist diagram of the electrochemical impedance spectroscopy; S is the effective area of the electrode (in cm 2 ).
[0084] Cycle performance test:
[0085] Place the lithium-ion battery in a 45℃ constant temperature box, let it stand for 30 minutes, charge it to 4.28V at a constant current of 5.24C, then charge it to 0.6C at a constant voltage of 4.28V, let it stand for 15 minutes; then discharge it to 3V at a constant current of 10.5C, let it stand for 30 minutes. This is a charge and discharge cycle. Record the first discharge capacity of the lithium-ion battery as C1, then perform 1000 charge and discharge cycles in the same steps, and record the discharge capacity of the lithium-ion battery in the 1000th cycle as C 1000 .
[0086] The cycle capacity retention rate of lithium-ion batteries = (C 1000 / C1)×100%.
[0087] In the present application, the constant current charging rate in the cycle performance test is 5.24C, and the constant current discharging rate is 10.5C, which belongs to a high rate charge and discharge cycle process. The higher the above cycle capacity retention rate, the better the cycle performance of the lithium-ion battery under high rate charge and discharge conditions; the lower the above cycle capacity retention rate, the worse the cycle performance of the lithium-ion battery under high rate charge and discharge conditions.
[0088] Storage performance test:
[0089] Take the prepared lithium ion battery, charge it to 4.28V at a constant current of 0.6C, and let it stand for 15 minutes; discharge it to 3V at a constant current of 0.5C, and let it stand for 15 minutes; then discharge it to 1.5V at a constant current of 0.1C, and let it stand for 15 minutes; place the discharged lithium ion battery in a high temperature oven at 80°C for 24 hours, then take it out, measure the thickness of the lithium ion battery and record it as L1; then place the lithium ion battery in a high temperature oven at 80°C for 24 hours, then take it out, measure the thickness of the lithium ion battery and record it as L2.
[0090] Storage thickness expansion ratio = (L2 / L1-1) x 100%.
[0091] In this application, storage performance can be used to characterize the safety performance of lithium-ion batteries. The greater the storage thickness expansion rate, the more gas is produced during the storage of the lithium-ion battery, and the worse the safety performance of the lithium-ion battery; the smaller the storage thickness expansion rate, the less gas is produced during the storage of the lithium-ion battery, and the better the safety performance of the lithium-ion battery.
[0092] Example 1-1
[0093] <Preparation of positive electrode sheet>
[0094] The positive electrode active material NCM622 (molecular formula LiNi0.6 Co 0.2 Mn 0.2 O2), a binder polyvinylidene fluoride (PVDF), and a conductive agent conductive carbon black (Super P) are mixed, wherein the mass ratio of NCM622, PVDF and Super P is 96:2:2, and a solvent N-methylpyrrolidone (NMP) is added, and the mixture is evenly mixed under the action of a vacuum mixer to obtain a positive electrode slurry with a solid content of 75wt%; the positive electrode slurry is evenly coated on one side surface of a positive electrode current collector aluminum foil with a thickness of 12μm, and dried at 90°C to obtain a positive electrode sheet with a single-sided positive electrode material layer coated with a coating thickness of 100μm, and the above steps are repeated on the other side surface of the aluminum foil to obtain a positive electrode sheet with a double-sided positive electrode material layer coated, and then cold pressed and cut to obtain a positive electrode sheet with a specification of 74mm×867mm.
[0095] <Preparation of negative electrode sheet>
[0096] The negative electrode active material artificial graphite, fast ion conductor Li7La3Zr2O 12 , sodium carboxymethyl cellulose (CMC-Na), styrene-butadiene rubber (SBR), and carbon nanotubes (CNTs) are mixed in a mass ratio of 94:2:1.5:1.5:1, deionized water is added, and the mixture is mixed evenly under the action of a vacuum mixer to obtain a negative electrode slurry with a solid content of 45wt%; the negative electrode slurry is evenly coated on one side of a negative electrode current collector copper foil with a thickness of 10μm, and dried at 90°C to obtain a negative electrode sheet with a single-sided negative electrode material layer coated with a coating thickness of 100μm, and the above steps are repeated on the other side of the copper foil to obtain a negative electrode sheet with a double-sided negative electrode material layer coated, and then cold pressed and cut to obtain a negative electrode sheet with a specification of 78mm×875mm. Among them, the Dv50 (i.e., D1) of the negative electrode active material is 7μm, the Dv50 (i.e., D2) of the fast ion conductor is 0.5μm, and the Dv99 (i.e., D3) of the fast ion conductor is 3μm.
[0097] <Preparation of Electrolyte>
[0098] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed uniformly in a volume ratio of 1:1:1 to obtain an organic solvent. LiPF6 is dissolved in the above organic solvent, and vinylene carbonate is added and mixed uniformly to obtain an electrolyte. Wherein, based on the total mass of the electrolyte, the mass percentage of LiPF6 is 12.5%, the mass percentage of vinylene carbonate is 3%, and the balance is the organic solvent.
[0099] <Preparation of Separator>
[0100] A cellulose membrane with a thickness of 20 μm (provided by Jiangsu Zhuogao Company) was used. The scanning electron microscope image of the cellulose membrane is shown in Figure 2 shown.
[0101] <Preparation of lithium-ion batteries>
[0102] The positive electrode sheet, the above-mentioned separator, and the negative electrode sheet are stacked in sequence, with the separator being placed between the positive electrode sheet and the negative electrode sheet to play an isolating role. The electrode assembly is then wound into an electrode assembly, which is then placed in an aluminum-plastic film and dried at 150°C for 12 hours. The electrolyte is injected and sealed, and then a lithium-ion battery is obtained after standing, forming, shaping and other processes.
[0103] Example 1-2 to Example 1-11
[0104] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1-1.
[0105] Example 2-1 to Example 2-6
[0106] Except that the milling time was adjusted so that the Dv50 and Dv99 of the fast ion conductor were as shown in Table 2, the rest was the same as Example 1-1.
[0107] Example 2-7 to Example 2-8
[0108] Except that the grinding time was adjusted so that the Dv50 of the negative electrode active material was as shown in Table 2, the rest was the same as Example 1-1.
[0109] Example 2-9 to Example 2-13
[0110] Except that the milling time was adjusted so that the Dv99 of the fast ion conductor was as shown in Table 2, the rest was the same as Example 1-1.
[0111] Example 2-14 to Example 2-19
[0112] Except for adjusting the relevant preparation parameters according to Table 2, the rest is the same as Example 1-1.
[0113] Example 2-20 to Example 2-21
[0114] Except that the milling time was adjusted so that the Dv50 and Dv99 of the fast ion conductor were as shown in Table 2, the rest was the same as Example 1-1.
[0115] Comparative Example 1
[0116] Except for using a polyethylene diaphragm (provided by Jiangsu Zhuogao Company) in <Preparation of diaphragm>, the rest is the same as Example 1-1.
[0117] Comparative Example 2
[0118] Except that a polyethylene diaphragm (provided by Jiangsu Zhuogao Company) is used in <Preparation of diaphragm> and the drying temperature after injecting electrolyte and sealing is adjusted to 90°C in <Preparation of lithium-ion battery>, the rest is the same as Example 1-1.
[0119] Comparative Example 3 to Comparative Example 4
[0120] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1-1.
[0121] The preparation parameters and electrical performance parameters of each embodiment and comparative example are shown in Tables 1 and 2.
[0122] Table 1
[0123]
[0124] Note: (1) In Table 1, “ / ” indicates no relevant preparation parameters; (2) “0.5 (90°C)” in Comparative Example 2 in Table 1 indicates that the thermal shrinkage rate of the polyethylene diaphragm at 90°C is 0.5%.
[0125] Referring to Table 1, it can be seen from Examples 1-1 to 1-11 and Comparative Examples 1 to 4 that when a fast ion conductor is added to the negative electrode system of a lithium ion battery, and the lithium ion battery uses a high temperature resistant diaphragm, and the mass percentage of the fast ion conductor and the heat shrinkage rate of the high temperature resistant diaphragm at 150°C are within the scope of this application, the lithium ion battery has a higher cycle capacity retention rate and a lower storage thickness expansion rate, thereby indicating that the cycle performance and safety performance of the lithium ion battery are improved. In Comparative Example 1, the lithium ion battery uses a polyethylene diaphragm, and the drying temperature after injecting the electrolyte and sealing is 150°C. At this time, the measured heat shrinkage rate of the diaphragm at 150°C is 35.0%. The heat shrinkage rate of the diaphragm is too high, and the diaphragm shrinks severely, and the prepared lithium ion battery cannot be tested for electrical performance. In Comparative Example 2, the lithium-ion battery uses a polyethylene diaphragm, and the drying temperature after injecting the electrolyte and sealing is 90°C. The storage thickness expansion rate of the lithium-ion battery is relatively high. This is because the drying temperature is relatively low, the water content of the lithium-ion battery is relatively high, the lithium-ion battery produces more gas, and the safety performance is poor. In Comparative Examples 3 and 4, the mass percentage of the fast ion conductor is too low, and an effective solid-state electrolyte membrane cannot be formed on the surface of the artificial graphite, resulting in poor cycle performance of the lithium-ion battery; the mass percentage of the fast ion conductor is too high, which will cause the mass percentage of the artificial graphite to be too low, which will affect the cycle performance and energy density of the lithium-ion battery.
[0126] It can be seen from Examples 1-1 to 1-5 that as the mass percentage of the fast ion conductor increases, the storage thickness expansion rate of the lithium ion battery also increases. This is because the fast ion conductor absorbs trace amounts of moisture. The higher the mass percentage of the fast ion conductor, the higher the water content in the lithium ion battery, the higher the residual water content in the lithium ion battery after drying, the more gas generated during storage, and the higher the storage thickness expansion rate of the lithium ion battery.
[0127] The type of high temperature resistant diaphragm usually affects the cycle performance and safety performance of lithium-ion batteries. It can be seen from Examples 1-1 and 1-6 to 1-9 that by selecting the above-mentioned high temperature resistant diaphragm, the lithium-ion battery has a higher cycle capacity retention rate and a lower storage thickness expansion rate, which shows that the cycle performance and safety performance of the lithium-ion battery are improved. It can be seen from Examples 1-1 and 1-9 that the cycle capacity retention rate of the lithium-ion battery when using a cellulose diaphragm is greater than the cycle capacity retention rate of the lithium-ion battery when using a spandex diaphragm. This is because the porosity of the cellulose diaphragm is larger, which is more conducive to the transmission of lithium ions, thereby improving the cycle performance of the lithium-ion battery.
[0128] The thickness H1 of the high temperature resistant diaphragm will affect the cycle performance, safety performance and energy density of the lithium-ion battery. It can be seen from Examples 1-6, 1-10 and 1-11 that by adjusting the value of H1 within the scope of this application, the lithium-ion battery has a higher cycle capacity retention rate and a lower storage thickness expansion rate, which means that the lithium-ion battery has good cycle performance and safety performance. In addition, as the thickness of the high temperature resistant diaphragm increases, the cycle capacity retention rate of the lithium-ion battery decreases. This is because the increase in the thickness of the high temperature resistant diaphragm will cause the transmission distance of lithium ions to be longer and the impedance to increase, thereby affecting the cycle performance of the lithium-ion battery. However, when the thickness of the high temperature resistant diaphragm is within the scope of this application, the lithium-ion battery has good cycle performance. From Figure 2 It can be seen that the cellulose separator includes fibers that are staggered in three dimensions. The cellulose separator has a large porosity, which facilitates the transmission of lithium ions and is beneficial to improving the cycle performance of lithium-ion batteries.
[0129] Table 2
[0130]
[0131] The ratio D2 / D1 of the Dv50 of the fast ion conductor to the Dv50 of the negative electrode active material and the value of the Dv50 (i.e., D2) of the fast ion conductor will also generally affect the cycle performance and safety performance of the lithium-ion battery. It can be seen from Example 1-1, Example 2-1 to Example 2-6, Example 2-20, and Example 2-21 that by regulating the values of D2 / D1 and D2 within the scope of this application, the lithium-ion battery has a higher cycle capacity retention rate and a lower storage thickness expansion rate, which indicates that the lithium-ion battery has better cycle performance and safety performance. In addition, as the Dv50 of the fast ion conductor increases, the storage thickness expansion rate of the lithium-ion battery decreases. This is because as the particle size of the fast ion conductor increases, the specific surface area of the fast ion conductor decreases, the fast ion conductor absorbs less water, the less gas is produced during storage, and the storage thickness expansion rate of the lithium-ion battery decreases.
[0132] The Dv50 (i.e., D1) of the negative electrode active material also generally affects the cycle performance and safety performance of the lithium-ion battery. It can be seen from Examples 1-1, 2-7, and 2-8 that by adjusting the value of D1 within the scope of this application, the lithium-ion battery has a higher cycle capacity retention rate and a lower storage thickness expansion rate, which indicates that the lithium-ion battery has better cycle performance and safety performance. It can be seen from Examples 2-7 and 2-8 that the Dv50 of artificial graphite is smaller, the Dv50 of the fast ion conductor is unchanged, the difference between the particle size of artificial graphite and the particle size of the fast ion conductor is relatively small, the distribution of the fast ion conductor on the surface of artificial graphite is relatively uneven, and the particle size of artificial graphite is smaller, which will affect the cycle performance of the lithium ion battery, but when the Dv50 of artificial graphite is within the scope of this application, the lithium ion battery has good cycle performance; the Dv50 of artificial graphite is larger, the Dv50 of the fast ion conductor is unchanged, the difference between the particle size of artificial graphite and the particle size of the fast ion conductor is relatively large, and the distribution of the fast ion conductor on the surface of artificial graphite is relatively uniform, but the particle size of artificial graphite is larger, which will affect the rate performance of the lithium ion battery and the cycle performance at a large rate, but when the Dv50 of artificial graphite is within the scope of this application, the lithium ion battery has good rate performance and cycle performance at a large rate.
[0133] The ratio D2 / D3 of the Dv50 of the fast ion conductor to the Dv99 of the fast ion conductor will also generally affect the cycle performance and safety performance of the lithium-ion battery. It can be seen from Examples 1-1, 2-9 to 2-13 that by regulating the value of D2 / D3 within the scope of this application, the lithium-ion battery has a higher cycle capacity retention rate and a lower storage thickness expansion rate, which indicates that the lithium-ion battery has better cycle performance and safety performance. In addition, as the Dv99 of the fast ion conductor increases, the value of D2 / D3 decreases, and the storage thickness expansion rate of the lithium-ion battery decreases. This is because as the particle size of the fast ion conductor increases, the specific surface area of the fast ion conductor decreases, the fast ion conductor absorbs less water, the less gas is produced during storage, and the storage thickness expansion rate of the lithium-ion battery decreases.
[0134] The Dv99 (i.e., D3) of the fast ion conductor will also generally affect the cycle performance and safety performance of the lithium-ion battery. It can be seen from Examples 1-1, 2-9 to 2-13 that by adjusting the value of D3 within the scope of this application, the lithium-ion battery has a higher cycle capacity retention rate and a lower storage thickness expansion rate, which means that the lithium-ion battery has better cycle performance and safety performance. In addition, as the Dv99 of the fast ion conductor increases, the storage thickness expansion rate of the lithium-ion battery decreases. This is because as the particle size of the fast ion conductor increases, the specific surface area of the fast ion conductor decreases, the fast ion conductor absorbs less water, the less gas is produced during storage, and the storage thickness expansion rate of the lithium-ion battery decreases.
[0135] The ionic conductivity of the fast ion conductor and the type of fast ion conductor will also generally affect the cycle performance of the lithium ion battery. It can be seen from Examples 1-1, 2-14 to 2-19 that by regulating the ionic conductivity of the fast ion conductor and the type of the fast ion conductor within the scope of this application, the lithium ion battery has a higher cycle capacity retention rate, which indicates that the lithium ion battery has better cycle performance. In addition, the higher the ionic conductivity of the fast ion conductor, the faster the transmission rate of lithium ions, the higher the cycle capacity retention rate of the lithium ion battery, and the better the cycle performance of the lithium ion battery. It should be noted that, in this article, relational terms such as first and second are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. Moreover, the term "includes", "comprising" or any other variant thereof is intended to cover non-exclusive inclusion, so that the process, method or article including a series of elements includes not only those elements, but also includes other elements that are not explicitly listed, or also includes elements inherent to such a process, method or article.
[0136] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.
[0137] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
Claims
1. A secondary battery, comprising a positive electrode sheet, a negative electrode sheet and a separator, wherein the separator is arranged between the positive electrode sheet and the negative electrode sheet, the negative electrode sheet comprises a negative electrode current collector and a negative electrode material layer arranged on at least one surface of the negative electrode current collector, the negative electrode material layer comprises a negative electrode active material and a fast ion conductor, at least part of the fast ion conductor is arranged on the surface of the negative electrode active material, and the fast ion conductor is lithium lanthanum zirconium oxide; based on the total mass of the negative electrode material layer, the mass percentage of the fast ion conductor is 0.1% to 16%; The thermal shrinkage rate of the diaphragm at 150° C. is less than or equal to 1.5%.
2. The secondary battery according to claim 1, wherein The thermal shrinkage rate of the diaphragm at 150° C. is less than or equal to 0.6%.
3. The secondary battery according to claim 1, wherein The separator includes one of a cellulose separator, a polyimide separator, a polyester separator, an aramid separator or a spandex separator.
4. The secondary battery according to claim 1, wherein The thickness of the diaphragm is H1 μm, 5≤H1≤30.
5. The secondary battery according to claim 1, wherein The Dv50 of the negative electrode active material is D1 μm, the Dv50 of the fast ion conductor is D2 μm, D2 / D1≤0.1, and 0.05≤D2≤1.
6. The secondary battery according to claim 5, wherein The secondary battery satisfies at least one of the following characteristics: (1) 0.03≤D2 / D1≤0.07; (2)0.3≤D2≤0.7; (3)5≤D1≤20。 7. The secondary battery according to claim 5, wherein The Dv99 of the fast ion conductor is D3 μm, and 0.15≤D2 / D3<1.
8. The secondary battery according to claim 7, wherein 0.5<D3≤4。 9. The secondary battery according to claim 1, wherein The ionic conductivity of the fast ion conductor is 1.44×10 - 5 S / m to 1.09×10 -3 S / m.
10. The secondary battery according to claim 1, wherein The lithium lanthanum zirconium oxide has a molecular formula of any one of formula (A), formula (B) or formula (C): <h2 style=";text-align:left;direction:ltr">Li<h2 style=";text-align:left;direction:ltr"> α <h2 style=";text-align:left;direction:ltr"> M<h2 style=";text-align:left;direction:ltr"> β <h2 style=";text-align:left;direction:ltr"> La3Zr2O<h2 style=";text-align:left;direction:ltr"> 12 <h2 style=";text-align:left;direction:ltr"> (A) In formula (A), M includes at least one of Ga, Al or Fe, satisfying: α+3β=7, α≥5.5, β≥0; Li7La γ R δ Zr2O 12 (B) In formula (B), R is at least one of Ce or Y, satisfying: 3γ+3δ=9, γ≥2.5, δ≥0; Li7La3Zr a X b Q c O 12 (C) In formula (C), X and Q are each independently selected from at least one of Ta, Nb, Sn, Sb, W, Te, Cr or Y, satisfying: a+b+c=2, a≥1, b≥0, c≥0.
11. The secondary battery according to claim 10, wherein The lithium lanthanum zirconium oxide includes Li7La3Zr2O 12 , Li 6.28 Al 0.24 La3Zr2O 12 , Li 6.25 Ga 0.25 La3Zr2O 12 , Li 6.4 Ga 0.2 La3Zr2O 12 、Li7La 2.5 Ce 0.5 Zr2O 12 、Li7La 2.875 Y 0.125 Zr2O 12 or Li7La3ZrNb 0.5 Y 0.5 O 12 At least one of .
12. The secondary battery according to claim 1, wherein The negative electrode material layer further includes a binder and a conductive agent. Based on the total mass of the negative electrode material layer, the mass percentage of the negative electrode active material is 80% to 98%, and the sum of the mass percentages of the binder and the conductive agent is 1% to 4%. 13 . An electronic device comprising the secondary battery according to claim 1 .